Understanding posterior meniscal roots lesions: from basic science to treatment() - Cruz, Raphael Serra (Rev Bras Ortop, 2017)
The variability of symptoms and the fact that they are not easily recognized in imaging studies make the diagnosis and treatment of posterior meniscal roots lesions a challenging task to the orthopedist. In recent years, a more precise understanding of the anatomy and biomechanical impair of the knee joint in these cases has enabled great advances in therapeutic approaches. Well-documented studies have shown that the repair of these lesions presents superior functional and clinical improvement when compared with meniscectomy. However, the progression of degenerative joint changes in the long-term still exhibits conflicting results.